Implementación para la Creación de un Centro Adulto Mayor en la Ciudad de Villavicencio - Meta - Sánchez Valcárcel, Nilsson Giovanni (Universidad Antonio Nariño, 2021)
According to information from the chamber of commerce of this city, there are no models in centers for the elderly in the city of Villavicencio, where they provide family members, who in turn, due to their working hours, show the absence of special and inappropriate care for them, where they are forced to take the favor or daily payment of the care of a neighbor, friend, relative or children, counteracting the social bond and professional medical care. By means of this need, what is sought is the creation of a limited micro-company where an accurate and realtime information provides adequate early warning of vital signs, nutrition, control and family union and in case of an emergency, a company is indirectly hired. of medical glued service so that the responsibility is stronger in front of the foundations already created with the union of a group of direct employees in aid of policies, norms and rights in contribution of society to adapt to changes show that the dignity of the older people is a calling with growing demand.